THU0543 Obesity and Osteoarthritis in Canada: Projections from a Microsimulation Model. (23rd January 2014) - Kopec, J. A.; Sayre, E. C.; Fines, P.; Flanagan, W. M.; Nadeau, C.; Okhmatovskaia, A.; Wolfson, M. C.
Abstract : Background: Osteoarthritis (OA) is the most common type of arthritis and, because of its strong association with age, a growing health problem around the world. A key modifiable risk factor for OA is body mass index (BMI). Therefore, changes in the distribution of BMI in the population can be expected to impact the incidence and, consequently, the prevalence of OA. However, we do not know how much the prevalence of OA would change as a result of changes in BMI. The question is important for estimating the benefits of interventions targeting obesity as well as projecting the burden of OA. Objectives: Our goal was to project the prevalence of OA in Canada over the next two decades, under a broad range of scenarios for changes in the distribution of BMI. Methods: We used a previously described Canadian micro-simulation model of OA called POHEM-OA [1 ]. The model simulates individual life and health histories for 25 million Canadians age 20+. Demographic and epidemiological parameters relevant to BMI and OA were derived from Canadian vital statistics, census data, national surveys, and administrative data in the province of British Columbia (physician-diagnosed OA). Obesity prevalence and OA incidence and prevalence rates were projected for the years 2001-2030. We considered a base-case (no intervention) scenario and a range of counterfactual (intervention) scenarios in which BMI for persons in selected BMI categories was increased or decreased by 0.1 to 2 units per year, starting in 2011. Results: In the base-case scenario, obesity (BMI≥30) prevalence in Canada increased from 18.8% in 2010 to 25.9% in 2030, while OA prevalence rose from 13.9 to 18.4%. Obesity was higher in men than in women in the base-case scenario, but became higher in women as a result of BMI-reducing interventions. OA prevalence was higher in women than in men in all scenarios. In the intervention scenarios, overall obesity rates in 2030 were 12.4%, 7.1%, and 1.8%, respectively, for a 0.3, 0.5 and 1 unit drop in BMI per year in overweight and obese individuals. In these scenarios, OA prevalence in 2030 reached 17.7%, 17.2% and 16.4%, respectively, a reduction of the expected (base-case) growth in OA by 16-44%. In the extreme scenario, in which obesity was virtually eliminated (drop in BMI by 2 units per year), OA prevalence still increased over time, reaching 15.8% by 2030 (less than half of the increase expected under the base-case scenario). In scenarios in which obesity levels increased at a higher-than-expected rate, OA prevalence increased faster, reaching 22.2% in 2030 in a scenario in which >90% of the population were obese. Conclusions: The increasing trend in OA prevalence in Canada is not highly sensitive to small-to-moderate reductions in obesity. Larger reductions (>50%) are likely to slow down the trend substantially, but not reverse it. Due to aging of the population, OA will remain a major and growing health issue in Canada over the next 2 decades, regardless of the course of the obesity epidemic. References: Kopec JA, Sayre EC, Flanagan WM, Fines P, Cibere J, Rahman MM, Bansback NJ, Anis AH, Jordan JM, Sobolev B, Aghajanian J, Kang W, Greidanus NV, Garbuz DS, Hawker GA, Badley EM. Development of a population-based microsimulation model of osteoarthritis in Canada. Osteoarthritis Cartilage. 2010;18(3):303-11 Acknowledgements: The study was supported by a grant from the Canadian Institutes of Health Resaerch. Disclosure of Interest: None Declared